Biomarkers in the era of targeted therapy in giant cell arteritis and polymyalgia rheumatica: is it possible to replace acute-phase reactants? - Carvajal Alegria, Guillermo; Nicolas, Mathilde; van Sleen, Yannick (Frontiers in Immunology, 2023)
Research in giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) has become more and more important in the last decades. Physicians are facing several challenges to manage diagnosis, treatment, relapses of GCA and PMR patients. The search for biomarker could give elements to guide the physician’s decision. In this review we aimed at summarizing the scientific publications about biomarkers in GCA and PMR in the past decades. The first point raised by this review is the number of clinical situations in which biomarkers could be useful: differential diagnosis of either GCA or PMR, diagnosis of underlying vasculitis in PMR, prediction of relapse or complication, disease activity monitoring, choice and modification of the treatments. The second point raised by this review is the large number of biomarkers studied: from common markers like C-reactive protein, erythrocyte sedimentation rate or elements of blood count to inflammatory cytokines, growth factors or immune cell subpopulation. Finally, this review underlines the heterogeneity between the studies and proposes points to consider in studies evaluating biomarkers in general and particularly in the case of GCA and PMR.